Enabling innovation - Rowarth, Jacqueline; Parsons, Tony (New Zealand Science Review, 2011)
​The link between scientific research and economic development is intuitively understood, but difficult to prove. This means not only that increasing research investment requires a leap of faith, but also that guarding what money is invested has become paramount. The effect has been management lockdown in an attempt to guarantee no wastage and drive productivity. McKinsey Quarterly points out that very few executives know what it takes to improve productivity of knowledge workers such as scientists. Researchers from Dartmouth College School of Business suggest that the answer is a twist on Skunk Works®, which concentrates innovative effort on a topic, while closing the loop between ideas and results. Building dedicated innovation teams which are free to recruit people who are wayward thinkers is the first step. The teams must also be free from some of the constraints that prevail in the rest of the company. The big difference between innovation teams and Skunk Works is that the teams remain integrated with the main company. The big difference for the scientist is focus on topic and freedom in operation. With the reorganisation of the science system, New Zealand has the chance to create an environment in which scientists flourish, can be truly creative and innovative, and their developments will drive productivity and the economy.